Agricultural Weed Research: A Critique and Two Proposals. Issue 4 (December 2014) - Ward, Sarah M.; Cousens, Roger D.; Bagavathiannan, Muthukumar V.; Barney, Jacob N.; Beckie, Hugh J.; Busi, Roberto; Davis, Adam S.; Dukes, Jeffrey S.; Forcella, Frank; Freckleton, Robert P.; Gallandt, Eric R.; Hall, Linda M.; et al.
Abstract : Two broad aims drive weed science research: improved management and improved understanding of weed biology and ecology. In recent years, agricultural weed research addressing these two aims has effectively split into separate subdisciplines despite repeated calls for greater integration. Although some excellent work is being done, agricultural weed research has developed a very high level of repetitiveness, a preponderance of purely descriptive studies, and has failed to clearly articulate novel hypotheses linked to established bodies of ecological and evolutionary theory. In contrast, invasive plant research attracts a diverse cadre of nonweed scientists using invasions to explore broader and more integrated biological questions grounded in theory. We propose that although studies focused on weed management remain vitally important, agricultural weed research would benefit from deeper theoretical justification, a broader vision, and increased collaboration across diverse disciplines. To initiate change in this direction, we call for more emphasis on interdisciplinary training for weed scientists, and for focused workshops and working groups to develop specific areas of research and promote interactions among weed scientists and with the wider scientific community.